2016
DOI: 10.5001/omj.2016.34
|View full text |Cite
|
Sign up to set email alerts
|

Neck Circumference as a Useful Marker for Screening Overweight and Obesity in Children and Adolescents

Abstract: NC is significantly correlated with overweight and obesity. It can be used with great reliability to screen overweight and obesity in children, and to identify those with a high BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
28
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 12 publications
14
28
1
Order By: Relevance
“…Overall, this suggests that measures of NC and BMI contain similar information, and thus may fail to explain additional variability in the outcome when set as joint, rather than single, predictors. These results are consistent with studies where NC was able to classify individuals with elevated BMI (Hatipoglu et al 2010;Nafiu et al 2010;Katz et al 2014;Taheri et al 2016), although predicting BMI from NC may be of limited value if the goal is to move beyond BMI to more useful markers of metabolic risk.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Overall, this suggests that measures of NC and BMI contain similar information, and thus may fail to explain additional variability in the outcome when set as joint, rather than single, predictors. These results are consistent with studies where NC was able to classify individuals with elevated BMI (Hatipoglu et al 2010;Nafiu et al 2010;Katz et al 2014;Taheri et al 2016), although predicting BMI from NC may be of limited value if the goal is to move beyond BMI to more useful markers of metabolic risk.…”
Section: Discussionsupporting
confidence: 88%
“…As a relatively simple anthropometric measurement, NC, like WC, was proposed as an easy-to-employ proxy for metabolically harmful FM deposited in the upper body (Tchernof and Després 2013). Studies have shown that NC and WC associate with one another (Hatipoglu et al 2010;Nafiu et al 2010;Katz et al 2014;Hassan et al 2015;Taheri et al 2016;Castro-Piñero et al 2017), and that their degree of association with outcomes such as overweight/obesity, HOMA, and SBP is similar (Hatipoglu et al 2010;Androutsos et al 2012). At the same time, some have argued that NC is preferable to WC, as the former does not demonstrate pre-versus postprandial variation, depend on the consistency of measurements taken at the end of an expired breath, or necessitate the removal of clothing (Hatipoglu et al 2010;Nafiu et al 2010;Taheri et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…13 Similarly, larger cut-off values of NC for the prediction of overweight and obesity were also noted in an Iranian population-based study. 36 Another Iranian study by Taheri et al 16 also described the comparison in NC cut-offs, sensitivity and specificity values among different countries. A notable variation was observed in the cut-off values of NC, sensitivity and specificity across the countries.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings also suggest an action level lower than previous published studies. 13,16,36 Gender-and-ethnic differences in body size might partially explain the heterogeneity in the optimal cut-offs among different populations. Furthermore, differences in sensitivity, specificity of the NC measuring method in different studies may be explained due to sample size and age range (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation